Residents’ Attitude Towards Impacts From Tourism Development In Anzali Wetland, Iran - Mana, Khoshkam (2013)
Wetlands draw unique social, economic and environmental benefits and costs, both on national scale and global scale, particularly in the developing countries. Variation in its sediment supply and ecological systems stimulates diversity in wetlands continuum from permanently inundates, to seasonally inundated and to ephemerally inundated. In Iran, the appointed bodies have expressed concerns regarding to the existing wetlands tourism development and planning process. Whilst the Ramsar Convention agrees that this issue deserves attention, however, given the little documentation, wetlands in Iran are poorly understood in the context of their origin, development and characteristics. This thesis examines one approach in dealing with Iran‘s wetlands tourism development: by understanding the local residents‘ attitudes from three dimensions. This thesis envisages intellectual capacity on residents‘ attitudes is crucial to the interpretation of wetland multi-layered characteristics governing its development process. The socio-cultural dimension involves increases in the wetlands destruction and poor communication between local communities and the appointed authorities, in relation to conservation management plans. The economic dimension includes the correlation between the pollution, decreases in employment opportunity and increases in living cost. The environmental dimension relates to facilities construction and development and land reclamation for agriculture and deforestation (which are caused by inefficient and ineffective projects).